Pecking at Rebecca: Character(istics)s of Manderley as Symbolised in Hitchcock’s Hollywood Practices in Rebecca - Poole, Mark (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2023)
The current paper begins with an examination of the relationship between the producer David O. Selznick and the director Alfred Hitchcock, making the case that there are parallels between their relationship and the unnamed protagonist and other characters in Hitchcock’s first Hollywood feature, Rebecca (1940). It then explores some of the Freudian and Lacanian symbols within the film and how these can allude to character traits of the main protagonists.